2020
DOI: 10.3390/min10100840
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fast-Growing Trees on Soil Properties and Carbon Storage in an Afforested Coal Mine Land (India)

Abstract: Surface coal mining activities have numerous consequences on terrestrial ecosystems. Loss of soil and biomass carbon pool due to mining activities is a serious concern in the rapidly changing environment. We investigated the effect of fast-growing trees (Albizia lebbeck, Albizia procera, and Dalbergia sissoo) on soil fertility and ecosystem carbon pool after eight years of afforestation in the post-mining land of Jharia coalfield, India, and compared with the adjacent natural forest site. Significant differenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…Reclamation of post-mining areas by afforestation is a promising ecological tool to offset greenhouse gas emissions and maintain the ecological balance in post-mining ecosystems [63][64][65][66].…”
Section: Discussionmentioning
confidence: 99%
“…Reclamation of post-mining areas by afforestation is a promising ecological tool to offset greenhouse gas emissions and maintain the ecological balance in post-mining ecosystems [63][64][65][66].…”
Section: Discussionmentioning
confidence: 99%
“…Different tree species play different roles in amending mine soil properties even in the same climate [38,[64][65][66]. Field experiment studies indicated significant differences in the SOC stocks under different afforested trees on the same soil substrate, which may be due to the amount of litter, the decomposition of dead roots, and the elemental composition of the individual biomass [37,67]. The decomposition of leaf litter releases the bound nutrients into the soil, which increases the SOC concentration of mine soils over time [62].…”
Section: The Effect Of Vegetation Types On Soc Accumulationmentioning
confidence: 99%
“…Our study, however, did not consider that different tree species have been shown to vary in their in uence on SOC sequestration. Several studies have demonstrated that, depending on the individual environmental setting, the tree species or tree type (e. g. deciduous vs. coniferous) used for recultivation is a potentially important or even key determinant for SOC sequestration 79,80,118,119 79 . These differences in SOC stocks are attributed to multi-level interactions between a number of in uence factors, including (i) the quantity of organic matter input via plant litter, (ii) the chemical composition of the above-and belowground litter, and (iii) resulting bioturbation and turnover processes facilitated by the soil (micro)biome 120 .…”
Section: Effect Of Recultivation Technologymentioning
confidence: 99%